CD40-mediated HIF-1α expression underlying microangiopathy in diabetic nerve pathology - Kan, Hung-Wei (Dis Model Mech, 2018)
To understand the pathology and molecular signatures of microangiopathy in diabetic neuropathy, we systemically and quantitatively examined the morphometry of microvascular and nerve pathologies of sural nerves. In the endoneurium of diabetic nerves, prominent microangiopathy was observed, as evidenced by reduced capillary luminal area, increased capillary basement membrane thickness and increased proportion of fibrin(+) blood vessels. Furthermore, capillary basement membrane thickness and the proportion of fibrin(+) blood vessels were correlated with small myelinated fiber density in diabetic nerves. In diabetic nerves, there was also significant macrophage and T cell infiltration, and cluster of differentiation 40 (CD40) expression was increased. The molecular alterations observed were upregulation of hypoxia-inducible factor-1α (HIF-1α), mitogen-activated protein kinase-activated protein kinase 2 (MK2; MAPKAPK2) and phosphatase and tensin homolog (PTEN). In addition, HIF-1α was correlated with small myelinated fiber density and capillary luminal area, while both MK2 and PTEN were correlated with capillary basement membrane thickness. The molecular cascades were further demonstrated and replicated in a cell model of microangiopathy on human umbilical vein endothelial cells (HUVECs) exposed to high-glucose medium by silencing of CD40, PTEN and HIF-1α in HUVECs using shRNA. These data clarified the hierarchy of the molecular cascades, i.e. upregulation of CD40 leading to HIF-1α expression in endothelium and nerve fibers. In conclusion, this study revealed the association of microangiopathy, thrombosis and inflammatory infiltrates with nerve degeneration in diabetic nerves, demonstrating that CD40 is a key molecule for the upregulation of HIF-1α and PTEN underlying the severity of microangiopathy.